Keanekaragaman Liana di Hutan Pendidikan Universitas Muhammadiyah Bengkulu, Kabupaten Bengkulu Tengah - Rusdi Hasan; Anggi Yuniarti; Kasmiruddin Kasmiruddin (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2018)
This study aims to determine the species of Liana plants found in Educational Forest of Muhammadiyah University of Centre Bengkulu withinConservation Forest of Bukit Barisan located in Kepahyang Regency of Bengkulu Province. This survey method research was conducted on March-April 2017. Sampling was collected in the plots placed along transect line in the forest which have temperature range from 27–31OC and humidity range 76-87%. The result found that of 20 Liana plants species belong to 9 families. Asteraceae family consist of 1 species of Mikania micrantha, family Araceae consist of 1 species of Pothos scandens, family Convolvulaceae consist of 4 species namely Ipomoea triloba, Ipomoea cairica, Merremia peltata, Merremia vitifolia, family Dioscorea consist of 1 species of Dioscorea hispida, family Fabaceae consist of 2 species of Calopogonium mucunoides, Centrosema pubescens, family Menispermaceae consist of 3 species of Cyclea barbata, Pericampylus glaucus, Tinospora crispa, family Palmae cinsist of 4 species namely Calamus caesius, Calamus manan, Daemonorops sabut, Korthalsia rigida, famili Piperaceae consist of 3 species of Piper betle, Piper nigrum, Piper ornatum, family Schizaeaceae consist of 1 species of Lygodium flexuosum.